2016
DOI: 10.1371/journal.pone.0150966
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Laminin Expression by Human Lung Epithelial Cells and Fibroblasts Cultured in Acellular Lung Scaffolds from Aged Mice

Abstract: The lung changes functionally and structurally with aging. However, age-related effects on the extracellular matrix (ECM) and corresponding effects on lung cell behavior are not well understood. We hypothesized that ECM from aged animals would induce aging-related phenotypic changes in healthy inoculated cells. Decellularized whole organ scaffolds provide a powerful model for examining how ECM cues affect cell phenotype. The effects of age on ECM composition in both native and decellularized mouse lungs were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…They showed that fibrotic ECM promotes TGF-β-independent myofibroblast differentiation compared with normal ECM 27. A recent study showed that aged mouse acellular lung matrix induced ECM components (laminin, elastin, fibronectin and collagen) in human bronchial epithelial cells and lung fibroblasts compared with young acellular lung matrix 28. The current study also showed that fibrotic acellular murine lung induces further TGF-β1 release from murine BMMC and PMC.…”
Section: Discussionsupporting
confidence: 63%
“…They showed that fibrotic ECM promotes TGF-β-independent myofibroblast differentiation compared with normal ECM 27. A recent study showed that aged mouse acellular lung matrix induced ECM components (laminin, elastin, fibronectin and collagen) in human bronchial epithelial cells and lung fibroblasts compared with young acellular lung matrix 28. The current study also showed that fibrotic acellular murine lung induces further TGF-β1 release from murine BMMC and PMC.…”
Section: Discussionsupporting
confidence: 63%
“…It has been shown that growth on aged ECM leads to significantly lower cellular expression of laminin α3 and α4 chains, which recapitulates the laminin deficiency that is observed in aged lung ECM. These data further highlight the deep biological information that is contained in the lung scaffold, and the feedback loops that exists between reparative cell populations and the underlying protein matrix (8). …”
Section: Introductionmentioning
confidence: 75%
“…Previous studies have indicated that 1) ECM retention after decellularization is higher in younger tissues, and 2) de novo matrix production and cell proliferation is increased after recellularization using younger rather than older tissues (52, 53). Taken together, these previous works predict that in the absence of species-specific cell-matrix interactions, our human ECs should perform better on rat and pig (younger) tissues rather than primate and human (older) tissues.…”
Section: Discussionmentioning
confidence: 99%